1986
DOI: 10.1111/j.1365-2125.1986.tb05216.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sulindac and indomethacin on the anti‐hypertensive and diuretic action of hydrochlorothiazide in patients with mild to moderate essential hypertension.

Abstract: 1 In this double-blind two period crossover study, we investigated the effect of indomethacin and sulindac on blood pressure in 25 hypertensive patients being treated with hydrochlorothiazide. The study consisted of seven 4 week periods. In the first and the last period the patients took placebos, in period two, four and six they were treated with hydrochlorothiazide 50 mg once daily alone, and in the third and fifth period hydrochlorothiazide 50 mg once daily was given in combination with either indomethacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 22 publications
1
5
0
1
Order By: Relevance
“…Sulindac has been observed to enhance the antihypertensive effect of di uretics in some studies [10,26], an effect related to its exclusively extrarenal prostaglandin inhibition. Other studies, however, have found sulindac to decrease renal thiazide clearance [21] and to have no effect on blood pressure in diuretic-treated patients [20,21]. Similar con troversial findings have been observed with indomethacin [20,21] and ibuprofen [10,22].…”
Section: Diureticssupporting
confidence: 72%
See 3 more Smart Citations
“…Sulindac has been observed to enhance the antihypertensive effect of di uretics in some studies [10,26], an effect related to its exclusively extrarenal prostaglandin inhibition. Other studies, however, have found sulindac to decrease renal thiazide clearance [21] and to have no effect on blood pressure in diuretic-treated patients [20,21]. Similar con troversial findings have been observed with indomethacin [20,21] and ibuprofen [10,22].…”
Section: Diureticssupporting
confidence: 72%
“…Hyporeninemic hypoaldosteronism has been demon strated in several studies in which NSAIDs were added to diuretics [10,18,20,21,28]. This development explains the increase in plasma potassium observed with the used NSAIDs.…”
Section: Diureticsmentioning
confidence: 91%
See 2 more Smart Citations
“…Derg. 26 (2) Bununla beraber damar duvarlarında PGI 2 sentezini stimüle ettiği ve direkt antihipertansif etkisinin PGI 2 ile alakalı olduğu iddia edilmektedir (28,34,35,36 …”
Section: Nsai̇i̇'larla Antihipertansif Ilaçlar Arasındaki Antagonizmadaunclassified